The impact of a gamified E-Learning environment in students attitude: a case study - Tenório, Marcos (2022)
E-learning conditions underpin the teaching and learning procedure and plan to involve students in their insight development process. Notwithstanding, including them during this procedure requires a high level of inspiration. Gamification is one of the methodologies that address this challenge and proposes that on-line situations are going to be a plus from it. On the other hand, Statistics is a field that can be supported by these learning methodologies. These days, with the use of massive data, the information holds a critical worth and to process this information into valuable data empowers the statistics field as a basic subject. This paper expects to feature a replacement point of view over the teaching and learning process offering a gamified e-learning condition to support the statistics field in the class. To research and portray the increases of this system, we refine a contextual investigation strategy to a Probability and Statistics lecture of an undergraduate Engineering course. With a descriptive study, we decide to comprehend the students’ attitudes once they face the proposed gamified e-learning condition. The results indicate that were some changes on students’ attitude when they use the gamified approach and suggest that we can be on the right track regarding the application of innovative learning formats, especially in the use of ICT.